Regulation 13D and the Regulatory Process - Jonathan R. Macey; Jeffry M. Netter (Washington University Law Quarterly, 1987)
Pursuant to its authority under the Securities Exchange Act of 1934, the Securities and Exchange Commission (SEC) has promulgated Schedule 13D, which imposes certain disclosure requirements on persons within ten days of the date that they acquire more than five percent of the beneficial ownership of a public company. This Article explores the economic and incentive effects of these disclosure requirements. After a brief introduction into the specifics of Item 4, the Article examines the effects of Item 4 under the prevailing assumption that these disclosure requirements actually provide target shareholders with new and useful information about the bidding firm's plans. Section II of the Article explores the assumption that Item 4 conveys any information of value to shareholders. In Section III we conclude that, to the extent it provides new information to the market, Item 4 will deter beneficial transactions. On the other hand, to the extent that Item 4 disclosures are redundant, they are wasteful, and they exacerbate the agency cost problems facing target firm shareholders because they provide incumbent management with a private right of action to use against hostile bidders in corporate control contests. Our analysis calls into question the desirability of the extensive legislation affecting the market for corporate control that deters tender offers and provides incumbent management with additional tools for resisting hostile tender offers. In our view, management has sufficient devices, and more than sufficient incentives, to mount resistance on its own. It is the bidders and not the targets who may be in need of any proffered regulatory assistance.
Keywords: Tender offers (Securities)